Nursing Documentation Variation Across Different Medical Facilities Within an Integrated Healthcare System. Issue 12 (December 2021) - Kang, Min-Jeoung; Rossetti, Sarah Collins; Knaplund, Christopher; Chang, Frank Y.; Schnock, Kumiko O.; Whalen, Kimberly; Gesner, Emily J.; Garcia, Jose P.; Cato, Kenrick D.; Dykes, Patricia C.
Abstract : The purpose of this study was to demonstrate nursing documentation variation based on electronic health record design and its relationship with different levels of care by reviewing how various flowsheet measures, within the same electronic health record across an integrated healthcare system, are documented in different types of medical facilities. Flowsheet data with information on patients who were admitted to academic medical centers, community hospitals, and rehabilitation centers were used to calculate the frequency of flowsheet entries documented. We then compared the distinct flowsheet measures documented in five flowsheet templates across the different facilities. We observed that each type of healthcare facility appeared to have distinct clinical care foci and flowsheet measures documented differed within the same template based on facility type. Designing flowsheets tailored to study settings can meet the needs of end users and increase documentation efficiency by reducing time spent on unrelated flowsheet measures. Furthermore, this process can save nurses time for direct patient care.